Enigma of Nickel Export Ban: Understanding Its Impact through Input-Output Analysis - Ine Ratna Dewi; Yordan Wiguna; Avior Ocean Louis Ishaac Noya (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
The nickel ore export ban policy has drawn pros and cons in various circles. This study aims to analyze the impact of the nickel ore export ban on other sectors of the economy and the interrelationship between one sector and another. This study uses secondary data in the form of Indonesia's Input Output Table Total Transactions at Basic Prices in 2016 derived from BPS publications and data on the number of Ferro-nickel exports in 2020 derived from UNData publications, which are then analyzed using the input-output method and presented using descriptive quantitative analysis. Based on the research results, electricity and gas procurement are the economic sectors with the most significant backward linkage. In contrast, the manufacturing sector achieves the most significant forward linkage value. In addition, the electricity and gas procurement sector also has the most significant output multiplier value, followed by the construction and manufacturing sectors. The increase in Ferro-Nickel exports due to the nickel ore export ban has considerably impacted the economy regarding both domestic and import output, especially in the manufacturing industry sector. Thus, nickel ore processing activities depend on capital goods and other imported raw materials. The study's implication shows that the export of Ferro-Nickel as part of the mining and quarrying sector impacts the output of other sectors to increase overall economic growth.